Promotion and Reviews of Gottfried Ostermeyer’s Book Erste Littauische Liedergeschichte (1793) in Eighteenth-Century Periodicals: A Subscription Notice (1792), Annotation (1793), and Review (1798) - Aleknavičienė, Ona (Senoji Lietuvos literatūra, 2016)
-